2008
DOI: 10.1177/0363546508316021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of National Football League Training Camp Injuries from 1998 to 2007

Abstract: Muscle strains are the most common injury type in practices. Contact type injuries are most common during pre-season games, and the number of significant injuries that occur during preseason games is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
204
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(231 citation statements)
references
References 20 publications
11
204
3
3
Order By: Relevance
“…Knee-sprain rates were also higher in competition than in practice at each competition level. This finding is consistent with the results of previous injury-surveillance studies that identified higher competition injury rates in high school athletics, 22 collegiate athletics, [23][24][25] professional football, 26 and professional soccer. 27,28 The observation highlights the increased intensity of game play that may occur within competitions versus practices.…”
Section: Overall Frequencies and Ratessupporting
confidence: 92%
“…Knee-sprain rates were also higher in competition than in practice at each competition level. This finding is consistent with the results of previous injury-surveillance studies that identified higher competition injury rates in high school athletics, 22 collegiate athletics, [23][24][25] professional football, 26 and professional soccer. 27,28 The observation highlights the increased intensity of game play that may occur within competitions versus practices.…”
Section: Overall Frequencies and Ratessupporting
confidence: 92%
“…A significantly longer recovery time was observed among National Football League athletes with hamstring re-injuries (56 days) compared to those with firsttime hamstring injury (16.5 days). (30) In a laboratory study, the lack of activated myogenic satellite cells within the fibrotic discontinuity area (scar tissue) was suggested to be the phenomenon responsible for the delay in healing of recurrent muscle injuries. (31) Female athletes with muscle injuries in the present study took a longer time (more than six weeks) to recover compared to male athletes.…”
Section: International Association Of Athletics Federations Worldmentioning
confidence: 99%
“…Among these, the hamstrings are consistently the most frequently injured. Similarly, in the National Football League (NFL) training camps from 1997 to 2007, hamstring strains were reported to be the second most common injury, after knee sprain [1]. Similarly, UEFA professional soccer data from 2001 to 2013 demonstrated that the hamstrings are the most frequently injured muscle group, accounting for 34 % of all muscle strains [2•].…”
Section: Epidemiology Of Muscle Injurymentioning
confidence: 99%
“…In a study of American football players, number of training camp days missed varied depending on which muscle group was injured [1]. [12].…”
Section: Return To Sports After Muscle Injurymentioning
confidence: 99%